ANALISIS SPEKTRUM GAYA MENGAJAR DIVERGENDALAM IMPLEMENTASI KURIKULUM 2013 - Aris Fajar Pambudi (Jurnal Pendidikan Jasmani Indonesia, 2014)
AbstractThe problems faced by the physical education teachers in teaching rooted in a different perception between thecomponents executing in the implementation of the curriculum and teaching physical education teachers sometimesdo not pay attention to the teaching style that is appropriate to the topic or material will be provided. The learningprocess of physical education in schools should refer to the applicable curriculum, the material that is taught at everylevel of education must be thoroughly selected and adapted to the stage of development and growth of children.This paper will try to analyze the teaching style that could be developed in 2013 curriculum. The Divergent teachingstyle is a form of problem solving in teaching. Stimuli given in divergent teaching styles can guide learners to findsolutions or answers individually.Key words: Analyze, divergent teaching style, 2013 curriculum.AbstrakPermasalahan dihadapi oleh guru pendidikan jasmani dalam pembelajaran bersumber pada persepsi yangberbeda diantara komponen-komponen pelaksana dalam implementasi kurikulum dan kadang guru pendidikanjasmani mengajar dengan tidak memperhatikan gaya dalam mengajarnya yang sesuai dengan topik atau materiyang akan diberikan. Proses pembelajaran pendidikan jasmani di sekolah harus mengacu pada kurikulum yangberlaku, materi yang diajarkan pada setiap jenjang pendidikan harus benar-benar dipilih dan disesuaikan dengantahap perkembangan dan pertumbuhan anak. Tulisan ini akan mencoba menganalisis gaya mengajar yang bisadikembangkan dalam kurikulum 2013. Gaya mengajar divergen merupakan suatu bentuk pemecahan masalah dalammengajar. Rangsangan-rangsangan yang diberikan dalam gaya mengajar divergen dapat membimbing peserta didikuntuk mencari pemecahan atau jawaban secara individual.Kata Kunci: analisis, gaya mengajar divergen, kurikulum 2013